Taylor-rule consistent estimates of the natural rate of interest - Claus Brand; Falk Mazelis (European Central Bank (ECB), 2019)
We estimate the natural rate of interest for the US and the euro area in a semi-structural model comprising a Taylor rule. Our estimates feature key elements of Laubach and Williams (2003), but are more consistent with using conventional policy rules: we model inflation to be stationary, with the output gap pinning down deviations of inflation from its objective (rather than relative to a random walk). We relax some constraints on the correlation of latent factor shocks to make the original unobserved-components framework more amenable to structural interpretation and to reduce filtering uncertainty. We show that resulting natural rate metrics are more consistent with estimates from structural models.
Keywords: C11; E32; E43; E52; 330; Natural Rate of Interest; Equilibrium Real Rate; Taylor Rule; Bayesian Estimation; Unobserved Components; Beveridge-Nelson Decomposition